Gold‐Catalyzed Direct Oxidative Arylation with Boron Coupling Partners. Issue 4 (21st December 2016) - Hofer, Manuel; Genoux, Alexandre; Kumar, Roopender; Nevado, Cristina
Abstract: An efficient synthesis of biaryls through a gold‐catalyzed oxidative cross‐coupling of arenes with strong electron‐deprived aryl boronates is presented herein. Regio‐ and chemocontrol are achieved by the selective activation of these coupling partners by gold at different oxidation states. Under reaction conditions devoid of basic additives or directing groups, the role of acetato ligand as an internal base has been revealed as a key parameter for expanding the reaction scope in these transformations. Abstract : Gold couple : A gold‐catalyzed synthesis of biaryls combining arenes and electron‐poor aryl boranes is presented. Under reaction conditions devoid of basic additives or directing groups, this methodology shows orthogonal reactivity and complementary scope with respect to existing methods. The high regio‐ and chemoselectivity stems from the specific reactivity of the reaction partners with gold at different oxidation states and the use of an acetato ligand as an internal base.